La motivación sostenida en el proceso enseñanza aprendizaje, un desafío en el aula de clase. - Mendoza Carrasco, Mariella Victoria (2016)
This article is of a theoretical nature, which will allow teachers to know the evolution of the concept of "School Motivation" and to analyze and interpret the different factors that intervene to maintain a "sustained and continuous motivation" in the teaching process - learning. In turn, it will allow you to know and use techniques, which will enable the interest and desire to learn with effort and constancy; Towards the achievement of appropriate ends and the realization of definite purposes as they are; The achievements of the objectives drawn in the different  pedagogical areas. The role of the teacher is to induce motives in his students, to arouse interest during the process of learning and behavior, and thus attract their attention, stimulating the desire to learn, maintaining a sustained motivation throughout the process.